Program Pengembangan dan Pemberdayaan Masyarakat (PPM) Bidang Pendidikan dan Kemandirian Ekonomi PT Sembilan Tiga Perdana - Masjon Parhusip; Eddy Winarno; Edy Nursanto (Publikasi Indonesia, 2022)
PT Sembilan Tiga Perdana is the holder of a Mining Business Permit for the Production Operation Stage, Administratively located in Katanjung Village, Kapuas Hulu District, Kapuas Regency, Central Kalimantan Province, PT Nine Tiga Perdanan strives to be able to realize the creation of a better and independent life for the community around the mine. how to implement the PPM Program effectively and accurately, so that in order to achieve this it is necessary to have a PPM Program that is right on target and in accordance with the conditions of the community around the mine. This study aims to provide recommendations for Community Development and Empowerment programs in the field of education and economic independence that are right on target and according to the needs of the local community. The research method was carried out by collecting primary data in the form of questionnaires and direct interviews with the community and secondary data in the form of blue prints in Central Kalimantan and literature studies. Data processing in this study uses descriptive statistical analysis in the form of sample analysis, data validation, data reliability, normality test and Friedman Two Way Anova test, direct observation of the condition of the local community also plays an important role in this study. The results of this study provide recommendations for 6 programs in the field of education and 6 programs in the field of economic independence that are right on target and according to the conditions of the local community in implementing the Community Development and Empowerment program.